The impact of patent litigation on shareholder value in the IT industry - Sangjun Nam; Changi Nam (International Telecommunications Society (ITS), 2012)
In recent years, patent lawsuits in the IT industry have become a sensitive issue. While numerous studies have investigated the wealth effect of patent and corporate litigation, few studies have examined the current patent litigation in the IT industry. This paper investigates the wealth effect of patent lawsuits using an event study method. This paper hypothesizes that a firm which initiates a lawsuit experiences more of a positive return than a rival firm when the patent lawsuit filing is announced, as a firm will initiate a lawsuit when they are convinced that they have a vantage position in the patent lawsuit. The empirical results show that a firm which has a vantage position in a patent lawsuit experiences a positive stock price return when they sue a rival firm for patent infringement and that a firm which does not have a vantage position in a patent lawsuit experiences a negative stock price return when they are sued by a rival firm. The empirical results support that a vantage position in patent litigation is the one of the key factors to explain the wealth effect of patent litigation. This paper suggests that action to increase patent competency to reach a vantage position in a patent war is one of the ways to increase shareholder value.
Keywords: 330; Patent litigation; Event study; Intellectual property; Litigation cost